Intraspecific variability through ontogeny in early ammonoids. Issue 1 (8th April 2013) - De Baets, Kenneth; Klug, Christian; Monnet, Claude
Abstract : Mollusks in general and ammonoids in particular are known to display a sometimes profound morphological intraspecific variability of their shell. Although this phenomenon is of greatest importance, it has rarely been investigated and quantified. It is especially crucial for taxonomy and incidentally for biodiversity analyses to account for it, because otherwise, the number of described species might exceed that of actual species within any group. Early ammonoids (Early Devonian, Paleozoic) typically suffer from this bias. For instance, most specimens from the same layer and the same region (e.g., the Erbenoceras beds of the Moroccan eastern Anti-Atlas studied here) differ morphologically from each other. Depending on the importance given to certain morphological characters, therefore, one could create a new species for almost every specimen. In this study, we measured nearly 100 such specimens from a restricted stratigraphic interval and quantified their intraspecific variability. There is a variable but strong overlap of the quantified shell characters at most ontogenetic stages, and only two species are here separated rather than the four previously recognized in Morocco. When ontogenetic trajectories of the Moroccan specimens are compared with coeval faunas from other regions (assigned to other species), a strong overlap between the morphospaces occupied by these taxa becomes apparent. The justification of some of these latter species is thus questionable even if their mean values in some conch parameters differ considerably from the mean values of the Moroccan species. Hence, the number of currently valid species of these loosely coiled early ammonoids is probably much too high. Extreme caution must therefore be taken when examining the diversity of groups in which the intraspecific variability is poorly known.